The Impact of Climate Change on Area-Based Disease Management - Sipra Barutu (Paspama Institute, 2025)
Climate change has become one of the major challenges in area-based disease management. This article investigates the impact of climate change on the dynamics and strategies of area-based disease management. We use historical climate data and climate change models to analyze its impact on disease spread, and explore adaptation and mitigation that can be applied in the context of area-based disease management. The results of this study indicate that climate change has affected the geographical distribution of diseases, seasonality of spread, and prevalence rates. In addition, this article also provides insights into strategic steps that can be taken to strengthen area-based disease management in the face of climate change challenges.